2002
DOI: 10.1074/jbc.m207162200
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Novel Maturation Mechanism and Restricted Substrate Specificity for the SspB Cysteine Protease ofStaphylococcus aureus

Abstract: The SspB cysteine protease of Staphylococcus aureus is expressed in an operon, flanked by the sspA serine protease, and sspC, encoding a 12.9-kDa protein of unknown function. SspB was expressed as a 40-kDa prepropeptide pSspB, which did not undergo autocatalytic maturation. Activity of pSspB was reduced compared with 22-kDa mature SspB, but it was equivalent to mature SspB after incubation with SspA, which specifically removed the pSspB N-terminal propeptide. SspC abrogated the activity of pSspB when incubated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
107
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(114 citation statements)
references
References 52 publications
(52 reference statements)
6
107
1
Order By: Relevance
“…Of note, 10 pseudogenes have arisen in ED98 since the most recent common ancestor with the human strain MR1, including several that would inf luence hostpathogen interactions (Table S2). For example, mutations leading to loss of function have occurred in genes encoding a putative surface-exposed lipoprotein, a protease SspA involved in the maturation of SspB that contributes to blood clot formation (17), and asp1 required for the surface expression of SraP, a cell wall-associated protein involved in the pathogenesis of infective endocarditis (18). In addition, a mutation leading to a premature stop codon in the gene encoding the major staphylococcal protein A (SpA) has occurred in strain ED98.…”
Section: The Poultry St5 Clade Has Diversified From Its Human Progenimentioning
confidence: 99%
“…Of note, 10 pseudogenes have arisen in ED98 since the most recent common ancestor with the human strain MR1, including several that would inf luence hostpathogen interactions (Table S2). For example, mutations leading to loss of function have occurred in genes encoding a putative surface-exposed lipoprotein, a protease SspA involved in the maturation of SspB that contributes to blood clot formation (17), and asp1 required for the surface expression of SraP, a cell wall-associated protein involved in the pathogenesis of infective endocarditis (18). In addition, a mutation leading to a premature stop codon in the gene encoding the major staphylococcal protein A (SpA) has occurred in strain ED98.…”
Section: The Poultry St5 Clade Has Diversified From Its Human Progenimentioning
confidence: 99%
“…A third gene in the ssp operon encodes a small protein, SspC, now commonly referred to as Staphostatin B, which we identified as an inhibitor of SspB (10) and for which others defined the structural basis of inhibition (12). The need for an inhibitor is supported by the finding that expression of SspB in Escherichia coli is lethal unless accompanied by Staphostatin B or a Cys 3 Ser active site mutant in SspB.…”
mentioning
confidence: 99%
“…SspA is expressed in an operon with a cysteine protease, SspB, and activates the zSspB zymogen by removing its N-terminal propeptide (10). Mature 20-kDa SspB mimics plasma serine proteases as noted by its ability to (i) convert high molecular weight kininogen into heavy and light chains, (ii) hydrolyze the Bz-Pro-Phe-Arg substrate of kallikrein, a serine protease that processes single chain kininogen by excision of the vasoactive peptide bradykinin (RPPGFSPFR), (iii) process the N terminus of the fibrinogen ␤-chain at the same site as plasmin, and (iv) remove the N-terminal domain of fibronectin with a specificity equivalent to plasminogen activator (10). We have also found that antibodies to SspB are produced when mice are challenged with hypervirulent strains of community-acquired methicillin-resistant S. aureus and that SspA and SspB are rapidly expressed in neutrophil vacuoles following phagocytosis (11), alluding to a role in modifying vacuolar proteins.…”
mentioning
confidence: 99%
“…1, C and E, and 3A). 1 The abbreviation used is: r.m.s.d., root mean square deviation. 2 The Schechter and Berger nomenclature refers to substrates as ϩ H 3 N-.…”
Section: Resultsmentioning
confidence: 99%
“…Staphostatins are the endogenous inhibitors of staphopains, the major secreted cysteine proteases from Staphylococcus aureus (1,2). Staphostatins are highly specific; although the targets of staphostatins A and B, staphopains A and B, are about 50% identical, the inhibitors do not cross-react.…”
mentioning
confidence: 99%